2024
DOI: 10.1038/s41598-024-55927-4
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive material characterization and component identification in sheet metal processing with electromagnetic methods

Bernd Wolter,
Benjamin Straß,
Kevin Jacob
et al.

Abstract: Electromagnetic methods for non-destructive evaluation (NDE) are presented, with which sheet metal components can be identified and their material properties can be characterized. The latter is possible with 3MA, the Micromagnetic Multiparametric Microstructure and stress Analyser. This is a combination of several micromagnetic NDE methods that make it possible to analyse the microstructure in a ferromagnetic material and to determine quantitative values of the mechanical material properties or the stress stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…EC-NDE systems not only detect the geometric features of metals, but can be used to detect and estimate different magnitudes of the material. Wolter et al [33] presented a combination of NDE methods that allows the microstructure of ferromagnetic metals to be analyzed. It obtains a 2D image of the material structure by using the proposed system.…”
Section: Non-destructive Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…EC-NDE systems not only detect the geometric features of metals, but can be used to detect and estimate different magnitudes of the material. Wolter et al [33] presented a combination of NDE methods that allows the microstructure of ferromagnetic metals to be analyzed. It obtains a 2D image of the material structure by using the proposed system.…”
Section: Non-destructive Evaluationmentioning
confidence: 99%
“…In addition to applications that directly use eddy currents, different studies [32][33][34][35] have shown that some materials exhibit a high-frequency diamagnetic response due to the reverse magnetic field induced by them. These investigations demonstrate that diamagnetic materials have great potential to be used in electromagnetic shielding and attenuation systems.…”
Section: Introductionmentioning
confidence: 99%